PENERAPAN RFID PADA SISTEM INFORMASI PENCATATAN PERSEDIAAN BARANG DI PT. PRIMA SEJATI SEJAHTERA KOTA BOYOLALI - Bagus Sudirman; Ahmad Ashifuddin Aqham; Indra Ava Dianta; Aqnes Wulandari (CV. Denasya Smart Publisher, 2024)
A system is a series of data or more than one component that is connected and interacts with each other to achieve certain goals (Sallaby & Kanedi 2020). Radio Frequency Identification or what is called RFID is a small electronic device consisting of a chip and an antenna. The aim of this research is to make data input easier, save time and produce more detailed and clear data. This type of research is qualitative descriptive research. The research results obtained regarding the use of the Radio Frequency Identification (RFID) system are that by scanning the Radio Frequency Identification (RFID) data it can be input automatically, there will be no double scans, and the data can be seen in detail and in detail.